Metronidazole activation and isolation of Clostridium acetobutylicum electron transport genes. - Santangelo, J D (1991)
An Escherichia coli F19 recA, nitrate reductase-deficient mutant was constructed by transposon mutagenesis and shown to be resistant to metronidazole. This mutant was a most suitable host for the isolation of Clostridium acetobutylicum genes on recombinant plasmids, which activated metronidazole and rendered the E. coli F19 strain sensitive to metronidazole. Twenty-five E. coli F19 clones containing different recombinant plasmids were isolated and classified into five groups on the basis of their sensitivity to metronidazole. The clones were tested for nitrate reductase, pyruvate-ferredoxin oxidoreductase, and hydrogenase activities. DNA hybridization and restriction endonuclease mapping revealed that four of the C. acetobutylicum insert DNA fragments on recombinant plasmids were linked in an 11.1-kb chromosomal fragment. DNA sequencing and amino acid homology studies indicated that this DNA fragment contained a flavodoxin gene which encoded a protein of 160 amino acids that activated metronidazole and made the E. coli F19 mutant very sensitive to metronidazole. The flavodoxin and hydrogenase genes which are involved in electron transfer systems were linked on the 11.1-kb DNA fragment from C. acetobutylicum.